Impact of climate change on human health: evidence from riverine island dwellers of Bangladesh. - Hossain, Babul; Shi, Guoqing; Ajiang, Chen; Sarker, Md Nazirul Islam; Sohel, Md Salman; Sun, Zhonggen; Hamza, Amir (International Journal of Environmental Health Research, 2022)
This study aims to explore the impact of climate change on health, including local adaptation strategies. A mixed-method approach has been used in this study. The results reveal that increasing the frequency of flooding, severity of riverbank erosion and drought, and rising disease outbreak are the highest indicators of climate change perceived by riverine island (char) dwellers, which is similar to the observed data. It also uncovers, approximately all respondents encounter several health-related issues during different seasons where prevailing cold and cough with fever, skin diseases, and diarrhoea are the leading ailments. Several adaptation strategies are accommodated by char inhabitants in order to enhance resilience against the climate change health impacts, but the paucity of money, disrupted communication, lack of formal health-care centre are the most obstacles to the sustainability of adaptation. This research recommends that healthcare-associated project should be performed through proper monitoring for exterminating char dwellers' health issues.